The hidden gold : a marie-grace mystery - Buckey, Sarah Masters, 1955- (American Girl, 2012)
"Marie-Grace can't wait to begin her journey up the Mississippi River with her father. The steamboat they're traveling on is the biggest and fanciest boat Marie-Grace has ever seen. It's crowded with all sorts of interesting passengers, including Wilhelmina Newman, a girl her age. Wilhelmina is traveling alone, and she's carrying a secret in one of her trunks--clues to hidden Gold Rush treasure. Marie-Grace and Wilhelmina have to unravel the clues to find the gold--and they're not the only ones looking for it! An illustrated "Looking Back" essay provides facts about the 1850s"--